PENERAPAN RESPONSIBILITAS KERJA DALAM MENINGKATKAN KINERJA APARATUR PELAYANAN PUBLIK DI KANTOR PERTANAHAN HALMAHERA BARAT - MEDJA, AGNESIA AGUSTIN; ROMPAS, WELSON; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2020)
Work responsibility is a measure to see government administrators carry out the authoritythey give and carry out in accordance with existing procedures and provisions, public bureaucracy is saidto be responsible if they carry out their duties as well as possible and are not just reasons, whethersomeone is supervising or not, by mobilizing all abilities it has effectively and efficiently. This study aimsto explain the application of work responsibility in improving the performance of public service personnel.To achieve these objectives researchers used qualitative methods using data collection techniques throughinterview, observation, and documentation. The result of research in the land office west Halmahera showthat all staff employes can be responsible for carrying out their positions, they can carry out the authoritygiven to them by their superiors, there are performance evaluation standards, the servives provided to thecommunity are good enough, agencies take service actions fair according to the work code of ethics, andthere is a commitment from the leadership by providing quality public service and having fast, easy, andclear procedures so that people are satisfied in completing their affairs. So that all staff can provide betterservice,it is hoped that the office building will be repaired and make improvements in strengthening theinternet network.Keywords: Work Responsibility, Performance, Public Service.